2021
DOI: 10.1007/s10708-021-10503-5
|View full text |Cite
|
Sign up to set email alerts
|

Geodemographic insights on the COVID-19 pandemic in the State of Wisconsin and the role of risky facilities

Abstract: The COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to impact the United States. While age and comorbid health conditions remain primary concerns in the community-based transmission of the virus, empirical evidence continues to suggest that substantial variability exists in the geographic and geodemographic distribution of COVID-19 infection rates. The purpose of this paper is to provide an alternative, spatiotemporal perspective on the pandemic using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Finally, recent research suggests that commercial activity, specifically the movement of people between work and home, is an important explanatory factor in the spread of COVID-19 ( Bontempi et al, 2021 ; Grubesic et al, 2021 ). Indeed, studies have shown a link between COVID-19 transmission in some communities where individuals are likely to work at “risky” facilities with the potential for high infection rates ( Towers et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent research suggests that commercial activity, specifically the movement of people between work and home, is an important explanatory factor in the spread of COVID-19 ( Bontempi et al, 2021 ; Grubesic et al, 2021 ). Indeed, studies have shown a link between COVID-19 transmission in some communities where individuals are likely to work at “risky” facilities with the potential for high infection rates ( Towers et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%